Estructuras escalonadas. Modelación física y formulación matemática (2019)
Open channel flow is governed by gravity forces and its effect on the flow behavior depends on the slope of the channel. Frequently the topography means it is necessary to take the flow from a high level to a low level in a relatively short distance, i.e., in a segment with a steeper slope, which produces high velocities. As a result, it is necessary to dissipate the excessive kinetic energy, either locally or gradually. Stepped structures, the topic of study of this research, allow energy to dissipate in open channel flows gradually. After compiling and studying different research about stepped structures, it is necessary to continue to studying the flow behavior on these types of structures. Following the recommendations of various authors, future research should be focused on developing a design methodology that so far hasn’t been achieved. The methodology of this research consists of building three physical models of stepped structures, studying and characterizing the flow through the structure and developing a design methodology. This study presents two equations to identify the type of flow in the structure, when the geometry of the structure and the flow rate are known. It is proposed a design methodology for skimming flow.